Violence on doctors. An observational study in Northern Italy - Firenze, Alberto; Santangelo, Omar Enzo; Gianfredi, Vincenza; Alagna, Enrico; Cedrone, Fabrizio; Provenzano, Sandro; La Torre, Giuseppe (La Medicina del Lavoro, 2020)
Background: Violence in the workplace is now universally recognized as a significant global public health issue and is one of the most serious issues affecting the healthcare sector. Objectives: To assess the prevalence of workplace violence. Methods: We performed a multicenter cross-sectional study using an anonymous questionnaire submitted to doctors from Northern Italy. The survey investigates socio-demographic information, the number of years of work in the health sector and the physical and verbal aggressions that occurred in the workplace in the last 12 months. Results: The sample consists of 4545 healthcare workers, of whom 2603 (57.27%) are females. The mean age of the sample is 49.79 years (SD ± 12.63). The risk of being victim of physical aggression at work in the last 12 months is significantly associated with the following independent variables: male gender (aOR 2.09, 95% CI 1.51-2.88), work in the public sector (aOR 2.57, 95% CI 1.72-3.85), being victim of verbal aggression at work in the last 12 months (aOR 22.52, 95% CI 10.97-46.20), work in the operational units of the Medical area (aOR 2.36, 95% CI 1.33-4.21) and the Territorial area (aOR 1.97, 95% CI 1.04-3.74). Discussion: The prevalence of violent behaviour is difficult to assess, because violent incidents are underreported or unreported. The results of the study suggest that increased awareness is necessary to develop effective control strategies at individual, hospital and national levels.